Biological effects in normal human fibroblasts following chronic and acute irradiation with both low- and high-LET radiation - Anello, Pasqualino; Esposito, Giuseppe (Frontiers in Public Health, 2024)
Radiobiological studies at low dose rates allow to improve the knowledge of the mechanisms by which radiation exerts its effects on biological systems following chronic exposures. Moreover, these studies can complement available epidemiological data on the biological effects of low doses and dose rates of ionizing radiation. Very few studies have simultaneously compared the biological effects induced by low-and high-LET radiations at the same dose rate for chronic irradiation. We compared, for the first time in the same experiment, the effects of chronic (dose rates as low as about 18 mGy/h and 5 mGy/h) and acute irradiations on clonogenicity and micronucleus formation in AG1522 normal human skin fibroblasts in the confluent state exposed to doses of low-and high-LET radiation (gamma rays and alpha particles) with the aim of investigating any differences due to the different radiation quality and different dose rate (in the dose range 0.006 -0.9 Gy for alpha particles and 0.4-2.3 Gy for gamma rays). As expected, alpha particles were more effective of gamma rays at inducing both cytogenetic damage and reduction of clonogenic cell survival. For gamma rays the cytogenetic damage and the reduction of clonogenic cell survival were greater when the dose was delivered acutely as opposed to chronically. Instead, for the alpha particles, at the same dose we found equal cytogenetic damage and reduction of clonogenic cell survival, for both chronic and acute exposure (except for the highest doses of 0.4 and 0.9 Gy where cytogenetic damage is greater at low dose rate). The results of this study may have an impact on space and terrestrial radioprotection of humans at low doses and low dose rates, on biodosimetry and on the use of ionising radiation in medicine. These results also provide insights into the understanding of damage induction and cell reaction mechanisms following chronic exposure (at dose rates as low as 18 mGy/h and 5 mGy/h) to low and high LET radiation.